Freedom from reality : the diabolical character of modern liberty - Schindler, D. C. (Catholic ideas for a secular world., 2017)
Presents a critique of the deceptive and ultimately self-subverting character of the modern notion of freedom, retrieving an alternative view through a new interpretation of the ancient tradition.